UJI PROPORSI POPULASI TANAMAN PADA TUMPANGSARI KUBIS BUNGA (Brassica oleracea L var. PM 126) DAN KACANG TANAH (Archis hypogaea var. Kancil) TERHADAP PERTUMBUHAN DAN HASIL - Pasha Rizki Faturrahman, Pasha; Supriadi, Devie Rienzani; Sugiono, Darso (Jurnal Agrotech, 2025)
Intercropping is a cropping pattern involving more than one crop grown simultaneously on the same area of land during a certain planting period. The proportion of plants is a composition of the number of plants on one land area with an adjusted planting distance. This study aims to determine plant growth and the best proportion of the number of plants based on the value of intercropping evaluation parameters in flower cabbage (Brassica oleracea L var. PM 126) and peanut (Arachis hypogaea var. Kancil). The research was conducted at the Experimental Field, Telukjambe Village, East Telukjambe Sub-district, Karawang Regency starting in January 2023 until April 2023. The research used an experimental method of single-factor Randomised Group Design (RAK) environmental design, with 5 replications, K1 = 100% flower cabbage (control), K2 = 25% flower cabbage and 75% peanut, K3 = 50% flower cabbage and 50% peanut, K4 = 75% flower cabbage and 25% peanut, K5 = 100% peanut (control). Data were statistically analysed with the F table test at 5% and the Least Significant Difference (BNT) test at the 5% level. The best proportion is treatment K4 = 75% flower cabbage and 25% peanuts by producing a Land Equivalency Value (NKL) of 1.13.